2000
DOI: 10.1007/s004640000218
|View full text |Cite
|
Sign up to set email alerts
|

Do prior abdominal operations alter the outcome of laparoscopically assisted right hemicolectomy?

Abstract: Although there is a trend toward more conversions because of adhesions in patients with a history of prior abdominal operations (p = 0.078), no increase in morbidity resulted. Therefore, laparoscopically assisted right hemicolectomy can be offered to patients with PAO, whose rate of adhesions can be expected to equal that of patients with NPAO.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
46
1

Year Published

2004
2004
2015
2015

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(52 citation statements)
references
References 23 publications
(19 reference statements)
5
46
1
Order By: Relevance
“…Only a few studies have investigated the impact of prior surgery on laparoscopic colorectal procedures. In a study on laparoscopically assisted right colectomy, Hamel et al [8] found that there were no differences in the operating time, blood loss, complication rate, or hospital stay between patients with and those without previous surgery. Although there was a trend toward conversion in those who had undergone prior abdominal operations, the morbidity was not increased.…”
Section: Discussionmentioning
confidence: 99%
“…Only a few studies have investigated the impact of prior surgery on laparoscopic colorectal procedures. In a study on laparoscopically assisted right colectomy, Hamel et al [8] found that there were no differences in the operating time, blood loss, complication rate, or hospital stay between patients with and those without previous surgery. Although there was a trend toward conversion in those who had undergone prior abdominal operations, the morbidity was not increased.…”
Section: Discussionmentioning
confidence: 99%
“…The conversion rate for LRH in this study was 4%, which compares favourably with the published literature. 21 The reasons for conversion were locally advanced disease and adhesions due to previous surgery. The outcomes for converted patients were good.…”
Section: -23mentioning
confidence: 99%
“…In this series of 200 patients, 52% of whom had had a previous laparotomy, only five required conversion to laparotomy because of extensive intraabdominal adhesions. Hamel et al [20] compared the morbidity rate following right hemicolectomy between patients with and without prior abdominal operation. The complication rates for the two groups were similar despite the presence of more adhesions in the previously operated group.…”
Section: Adhesionsmentioning
confidence: 99%